PELESTARIAN KEARIFAN LOKAL DI KABUPATEN PURWAKARTA : SEBUAH UPAYA STRATEGIS PEMERINTAH DAERAH - Setiawan, Agustina; Amellia, Neneng Widya; Rokhmat, Dicky Febriansyah (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2025)
The research aims to analyze the magnitude of the influence of Regional Government strategies on the effectiveness of preserving local wisdom in Purwakarta Regency using quantitative explanatory methods, data collection techniques through literature studies and field studies, sampling techniques using simple random sampling. The research results show that the implementation of the Regional Government's strategy in preserving local wisdom based on the strategic components purposes, environment, directions, actions and learning has been programmed quite well. Respondents' responses obtained a score of 1.78 or included in the quite good category. Then the preservation of local wisdom in Purwakarta Regency based on the theory of measuring the effectiveness of effort, impact, adequacy of performance, cost effectiveness of the process shows effective results. The results of the data analysis of respondents' responses were included in the quite good category, namely 1.96. Based on the results of the correlation analysis, there is a very strong relationship (0.8634) between the implementation of the Regional Government strategy and the effectiveness of preserving local wisdom in Purwakarta Regency, so the hypothesis has been tested empirically through field research